2005
DOI: 10.1140/epjc/s2005-02205-2
|View full text |Cite
|
Sign up to set email alerts
|

The statistical parton distributions: status and prospects

Abstract: New experimental results on polarized structure functions, cross sections for e ± p neutral and charge current reactions and ν (ν) charge current on isoscalar targets are compared with predictions using the statistical parton distributions, which were previously determined. New data on cross sections for Drell-Yan processes, single jet in pp collisions and inclusive π 0 production in pp collisions are also compared with predictions from this theoretical approach. The good agreement which we find with all these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
235
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(257 citation statements)
references
References 44 publications
19
235
2
Order By: Relevance
“…The statistical model of Ref. [10] and the SU(3) version of the Chiral Quark-Soliton model of Ref. [33] both predict positive distributions, while the Meson Cloud model of Ref.…”
Section: Polarised Pdfs From a Lo Fit To The Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical model of Ref. [10] and the SU(3) version of the Chiral Quark-Soliton model of Ref. [33] both predict positive distributions, while the Meson Cloud model of Ref.…”
Section: Polarised Pdfs From a Lo Fit To The Asymmetriesmentioning
confidence: 99%
“…Unpolarised lepton scattering [2][3][4], later confirmed by DrellYan production experiments [5,6], has revealed that the light-quark difference, u − d, is negative and much larger in absolute value than expected, resulting in a large violation of the Gottfried sum rule [7]. Model calculations that explain this asymmetry also provide predictions [8][9][10] for the polarised flavour asymmetry, ∆u − ∆d.…”
Section: Introductionmentioning
confidence: 99%
“…The QSM is therefore unbiased with respect to experimental results. A statistical model [159] which describes the nucleon as a gas of massless partons and a model based on the meson cloud picture [158].…”
Section: Resultsmentioning
confidence: 99%
“…Recent measurements of multiplicities and double spin asymmetries as a function of the final transverse momentum of pions in SIDIS at JLab [8,22] suggest that transverse momentum distributions may depend on the polarization of quarks and possibly also on their flavor. Calculations of transverse momentum dependence of TMDs in different models [30][31][32][33] and on lattice [34,35] indicate that the dependence of the transverse momentum distributions on the quark polarization and flavor may be very significant.…”
Section: Introductionmentioning
confidence: 99%